2004
DOI: 10.1016/s0093-934x(03)00436-x
|View full text |Cite
|
Sign up to set email alerts
|

Stress priming in picture naming: An SOA study

Abstract: This study investigates whether or not the representation of lexical stress information can be primed during speech production. In four experiments, we attempted to prime the stress position of bisyllabic target nouns (picture names) having initial and final stress with auditory prime words having either the same or different stress as the target (e.g., WORtel-MOtor vs. koSTUUM-MOtor; capital letters indicate stressed syllables in prime-target pairs). Furthermore, half of the prime words were semantically rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 21 publications
7
31
3
Order By: Relevance
“…Assuming that this patient had an impairment of lexical stress representations of irregular words, this result would support Levelt et al's theory (see also Laganaro, Vacheresse, & Frauenfelder, 2002;Miceli & Caramazza, 1993). However, Schiller, Fikkert, and Levelt (2004) did not obtain a metrical priming effect in Dutch, not even for irregular words, i.e., words that should be stored in the lexicon according to Levelt et al (1999).…”
Section: Metrical Stress In Dutchsupporting
confidence: 74%
See 1 more Smart Citation
“…Assuming that this patient had an impairment of lexical stress representations of irregular words, this result would support Levelt et al's theory (see also Laganaro, Vacheresse, & Frauenfelder, 2002;Miceli & Caramazza, 1993). However, Schiller, Fikkert, and Levelt (2004) did not obtain a metrical priming effect in Dutch, not even for irregular words, i.e., words that should be stored in the lexicon according to Levelt et al (1999).…”
Section: Metrical Stress In Dutchsupporting
confidence: 74%
“…Possibly, metrical stress is computed for the majority of the words as long as their stress pattern can be derived by some linguistic rule. This might also include words that are irregular according to psycholinguistic definitions, but regular in terms of certain linguistic theories (Trommelen & Zonneveld, 1989, 1990; see also Schiller et al, 2004). In this study, we will not be concerned with whether metrical stress is stored or computed.…”
Section: Metrical Stress In Dutchmentioning
confidence: 99%
“…The empirical evidence for whether or not metrical stress is stored in the lexicon is inconclusive at the moment (see overviews in Schiller et al, 2004Schiller et al, , 2006a. Possibly, metrical stress is computed for the majority of the words as long as their stress pattern can be derived by some linguistic rule including words that are irregular according to psycholinguistic definitions (see Fikkert et al, 2005 andSchiller et al, 2004).…”
Section: Metrical Stress In Dutchmentioning
confidence: 99%
“…Possibly, metrical stress is computed for the majority of the words as long as their stress pattern can be derived by some linguistic rule including words that are irregular according to psycholinguistic definitions (see Fikkert et al, 2005 andSchiller et al, 2004). Here, we will not be concerned with whether metrical stress is stored or computed.…”
Section: Metrical Stress In Dutchmentioning
confidence: 99%
“…In Dutch, this would be non-initial stress. However, recent experiments (Schiller, Fikkert, & Levelt, 2004) showed that even exceptional stress patterns might not be stored in the lexicon as long as they can be derived by rule.…”
Section: Introductionmentioning
confidence: 99%